Laser induced fluorescence in atmospheric pressure discharges. (26th May 2015) - Dilecce, G; Martini, L M; Tosi, P; Scotoni, M; De Benedictis, S
Abstract: This paper offers an outline of laser induced fluorescence (LIF) diagnostics and practical recommendations for its use in atmospheric pressure discharges. LIF principles, technical requirements and rationalization of experimental outcomes by modelling are addressed. Important issues that are particularly relevant to small scale, spatially inhomogeneous discharges, like plasma-jets, are emphasized. For the first time, all collision processes and the spatial non-homogeneity of the laser beam are together accounted for in the LIF model. Saturation characteristics are discussed and used for the assessment of model parameters. A calibration procedure is discussed and implemented. Gas temperature measurements by LIF are also addressed. The whole description of the technique is given, without loss of generality, through the example of its application to the OH radical. Notes on other diatomic radicals, CH, NO and CN, are given along the paper. Some results in a RF plasma-jet are presented as an example of application in a discharge system where all the concepts developed in the paper are applied.